Identification of oligomers in polyethyleneterephthalate bottles for mineral water and fruit juice - Development and validation of a high-performance liquid chromatographic method for the determination of first series cyclic trimer - Nasser, ALM; Lopes, LMX; Eberlin, M. N.; Monteiro, M. (Elsevier B.V., 2005)
Cyclic oligomers were identified in PET bottles used for mineral water and fruit juice using MS and H-1 and C-13 NMR: a first series cyclic trimer, a first series cyclic tetramer, a first series cyclic dimmer and a second series cyclic trimer. An analytical method to determine first series cyclic trimer in these bottles was developed and validated, using HPLC. The first series cyclic trimer levels were 316-462 mg/100 g of PET bottle. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: oligomers; PET bottles; HPLC; validation; MS; H-1 and C-13 NMR